The Socio-political Dynamics of the Citizen’s Revolution. Political Work as the ‘Art of Serving’ that Separates and Unites State and Society - Villarreal Velásquez, José Antonio (2018)
This article analyses the relations between politics and society during the so-called citizen’s revolution in Ecuador. Drawing on ethnographic research focused on political brokerage or the ‘art of serving’, the article analyses the particularities of political work by analysing the linkages and tensions that are constructed between the population of a suburb of the city of Guayaquil, the members of the governing political party of the Citizen’s Revolution, Movimiento Patria Altiva i Soberana (Alianza PAIS) and State functionaries. Meetings of political socialization and sectorial events- understood as institutional rituals- are taken as scenes in which to observe the interactions and the public performance of the protagonists of the pre-dominant political party in contemporary Ecuador.